Speed control of single phase motor / Sharifuddin Alaluddin and Badrul Zaman Abdullah - Alaluddin, Sharifuddin; Abdullah, Badrul Zaman (1991)
A number of motor control systems have been develop over the years to take advantage of variable speeds available from the armature voltage control of DC motors. A solid state electronic components is available to produce a varying DC voltage. So in order to give the most economical way to control the speed of single phase motor,here we use SCR controlled. These 'solid state electronic component usually provide manual adjustment for regulating the speed. For this project the drive circuit is classified into fullwave. The SCR conduction angle is controlled by setting a potentiometer. The component values for these project are those for 1/15 hp motor. in sizing components for higher horsepower ratings, the average steady state current and the stalled rotor current of the motor determine the current and power ratings of the SCRs, diodes, transformer and etc.